Storage of seeds of Cnidosculus phyllacanthus Pax & K. Hoffm. - Silva,Lígia M. de M. (2005)
This work aimed to determine the best environment for conservation of physiological quality of seeds of Cnidosculus phyllacanthus during storage. Seeds with 8.5% moisture content and 86% germinative capacity were filled in containers of different permeability, and storaged at different conditions during 360 days. Seeds packed in permeable container (paper bag) were stored at ordinary room temperature (18 to 25 ºC and 55 to 78% RH), and dry chamber (18 ºC and 60% RH) while those packed in semipermeable (polyethylene bag) and impermeable (glass) containers were stored in cold chamber (10 ºC and 75% RH). Seed moisture content, germinative capacity and germination speed were evaluated each 90 days interval. For all the tested storage conditions, seed germination speed was reduced at first evaluation and stabilized up to 360 days. Great deterioration in seeds stored at ordinary room condition was observed, while those stored in dry chamber maintained its germinative capacity for 270 days. The seed germinative capacity was better retained in cold storage, packaged either in semipemeable or impermeable containers. During storage, the seeds had a behavior classified as orthodox.